2010
DOI: 10.1371/journal.pntd.0000636
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography and Population Structure of Glossina fuscipes fuscipes in Uganda: Implications for Control of Tsetse

Abstract: Background Glossina fuscipes fuscipes, a riverine species of tsetse, is the main vector of both human and animal trypanosomiasis in Uganda. Successful implementation of vector control will require establishing an appropriate geographical scale for these activities. Population genetics can help to resolve this issue by characterizing the extent of linkage among apparently isolated groups of tsetse.Methodology/Principal FindingsWe conducted genetic analyses on mitochondrial and microsatellite data accumulated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
161
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 50 publications
(180 citation statements)
references
References 63 publications
18
161
1
Order By: Relevance
“…This lake runs east to west with multiple finger‐like inlets and wetland's across most of central Uganda. The extent of its wetlands and satellite lakes marks the eastern boundary of the G. f. fuscipes distribution and coincides with a clear genetic break between northern and southern Uganda G. f. fuscipes populations (Abila et al., 2008; Aksoy et al., 2013; Beadell et al., 2010, 2010). The updated habitat suitability model reflects this by identifying patchy habitat along the eastern margin of the G. f. fuscipes distribution (Figure 5b).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This lake runs east to west with multiple finger‐like inlets and wetland's across most of central Uganda. The extent of its wetlands and satellite lakes marks the eastern boundary of the G. f. fuscipes distribution and coincides with a clear genetic break between northern and southern Uganda G. f. fuscipes populations (Abila et al., 2008; Aksoy et al., 2013; Beadell et al., 2010, 2010). The updated habitat suitability model reflects this by identifying patchy habitat along the eastern margin of the G. f. fuscipes distribution (Figure 5b).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the major patterns of genetic differentiation were created under conditions of migration‐drift balance and that bottlenecks did not confound results in this study. This conclusion is also supported by previous population genetics studies that have shown evidence of ongoing gene flow among distinct populations separated by over 100 km (Abila et al., 2008; Beadell et al., 2010; Echodu et al., 2013; Hyseni et al., 2012; Opiro et al., 2017). Perhaps genetic drift contributes to high levels of genetic differentiation across small spatial scales and is counterbalanced periodically by rare long‐distance dispersal that connects populations along the habitat corridors identified in our analyses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations